2009
DOI: 10.1002/psc.1202
|View full text |Cite
|
Sign up to set email alerts
|

Azide reduction during peptide cleavage from solid support—the choice of thioscavenger?

Abstract: Peptide azides acquired growing impact because of application in bioconjugation via 'click chemistry' or Staudinger ligation. Furthermore, there are many methods established in organic synthesis addressing the reduction of azides to amines, but no observation of a reductive transformation of peptide azides during SPPS cleavage was yet reported. In the present study, the reduction of peptide azides during SPPS cleavage was investigated depending on the choice of thioscavenger, reacting as reductive species. Fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 44 publications
0
22
0
1
Order By: Relevance
“…As expected, no reductive side reaction of the azide-functionalized derivative was observed during the cleavage step of the lysine derivative from the resin (data not shown). [16] Both gH625-Pra and (C18) 2 L-N 3 were collected in good yields (20-40 % and 85 %, respectively) after HPLC-RP purification, and analyzed by mass spectrometry (MALDI-TOF), 1 H and 13 C NMR spectroscopy (for (C18) 2 L-N 3 ), and HPLC to confirm the compound identity and the purity.…”
Section: Resultsmentioning
confidence: 99%
“…As expected, no reductive side reaction of the azide-functionalized derivative was observed during the cleavage step of the lysine derivative from the resin (data not shown). [16] Both gH625-Pra and (C18) 2 L-N 3 were collected in good yields (20-40 % and 85 %, respectively) after HPLC-RP purification, and analyzed by mass spectrometry (MALDI-TOF), 1 H and 13 C NMR spectroscopy (for (C18) 2 L-N 3 ), and HPLC to confirm the compound identity and the purity.…”
Section: Resultsmentioning
confidence: 99%
“…We chose the azide function as a precursor for its ability to unleash an amine function under very mild conditions, such as the Staudinger reaction, which are compatible with the presence of orthogonal protecting groups such as Boc or Fmoc, and for its possible application to Huisgen’s 1,3-dipolar cycloaddition (click reaction). The azide function is stable to both Fmoc- and Boc- chemistries, provided that no sulfur-containing scavengers are used for the deprotection or the cleavage steps 26 . Thus, the introduction of this functional group in both Boc- and Fmoc-protected monomers can be used in a general strategy for the rapid construction of libraries of PNA-based compounds by solid-phase or off-resin modifications without the need of an extensive solution-based syntheses of many different modified PNA monomers.…”
Section: Resultsmentioning
confidence: 99%
“…[25] In a totally different context, Diederichsen and co-workers very recently reported that undesired azide reduction in a peptide depends on the position of the azide-containing moiety in the peptide. [26] Moreover, even though a variety of rea- gents have been used for the reduction of azides, in terms of their practical applicability, most of these methods have certain disadvantages, especially for a solid support. [18] Bartra and Vilarrasa and co-workers reported that tin(II) complexes, prepared by treatment of SnCl 2 or Sn(SR) 2 with appropriate amounts of RSH and tertiary amines, are efficient reducing agents for the transformation of azides to amines.…”
Section: Resultsmentioning
confidence: 99%